2018
DOI: 10.1017/s0261444818000125
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and instructed second language acquisition

Abstract: Interaction is an indispensable component in second language acquisition (SLA). This review surveys the instructed SLA research, both classroom and laboratory-based, that has been conducted primarily within the interactionist approach, beginning with the core constructs of interaction, namely input, negotiation for meaning, and output. The review continues with an overview of specific areas of interaction research. The first investigates interlocutor characteristics, including (a) first language (L1) status, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(131 citation statements)
references
References 280 publications
4
97
0
8
Order By: Relevance
“…Previous research has demonstrated that the effectiveness of recasts in leading to interlanguage development is influenced by several variables (see Loewen & Sato, , for a review). Of these, task complexity (i.e., inherent cognitive demands of tasks) and individual differences in L2 aptitude have been the focus of this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that the effectiveness of recasts in leading to interlanguage development is influenced by several variables (see Loewen & Sato, , for a review). Of these, task complexity (i.e., inherent cognitive demands of tasks) and individual differences in L2 aptitude have been the focus of this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore more noticeable in the language stream compared to a one‐letter bound morpheme (the future tense prefix). SLA research has widely reported that morphosyntactic features are some of the least commonly noticed features by language learners and are thus more difficult to acquire (Al‐Surmi, ; Behney et al, ; Cintrón‐Valentín & N. C. Ellis, ; N. C. Ellis, , , , ; N. C. Ellis & Collins, ; Godfroid, ; Godfroid & Uggen, ; Loewen & Sato, ; Simoens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…C. Ellis, , 2018N. C. Ellis & Collins, 2009;Godfroid, 2016;Godfroid & Uggen, 2013;Loewen & Sato, 2018;Simoens et al, 2018).…”
Section: Salience In Form Noticing and Production (Questions 1 And 2)unclassified
“…The pilot group was formed administratively, i.e. regardless of the experimental design, and included students with different learning abilities, in accordance with earlier conclusions about the effectiveness, under certain conditions, of teaching interactive communications to students with different levels of basic communicative skills within one group (Loewen & Sato, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In this approach, the object of study is interpersonal communication as a system of interactions between an individual and a social group, during which they comprehend one another's intentions, predict the interlocutor's reactions and carry out their own ones. Linguistic methodology considers the main models of interaction between communicants in Self/Other mode (social and individual characteristics of interlocutors, features of communicative goals, language manifestations) and methods for teaching these interactions, including their computer-mediated forms (East, 2016;Loewen & Sato, 2018).…”
Section: Problem Statementmentioning
confidence: 99%